SiRNA-Based Multivalent Vaccines: A Systematic Review of Potential Risks, Benefits, and Future Applications - Mohammad Nadeem Khan (International Journal of Vaccines, 2024)
Background: Small interfering RNA (SiRNA) technology represents a promising innovation in vaccine development, especially for multivalent vaccines that can target multiple pathogens or antigenic variants simultaneously. siRNA-based vaccines offer a unique mechanism to induce specific immune responses, presenting an adaptable and potentially powerful tool for tackling infectious diseases and cancer. Methods: This systematic review synthesizes recent studies on siRNA multivalent vaccines, focusing on their immunogenicity, safety, and effectiveness. We reviewed preclinical and clinical data from studies evaluating siRNA vaccine responses, safety profiles, delivery methods, and current regulatory challenges. Quantitative measures of immune response efficacy and reported adverse effects were extracted where available. Results: Findings demonstrate that siRNA-based multivalent vaccines can elicit robust immune responses against various targets, with promising adaptability to emerging pathogens. Preclinical studies report immune activation rates of up to [80%-85%] against targeted antigens, while initial clinical trials show [60%-70%] effectiveness in reducing pathogen load or tumor growth. Notably, the risk of vaccine escape mutants appears lower due to the multi-target approach, though concerns persist regarding potential off-target effects and challenges in achieving efficient siRNA delivery. Conclusions: siRNA-based multivalent vaccines hold transformative potential, particularly for their ability to be tailored for emerging infections and personalized therapies. Despite promising immunogenicity and adaptability, further research is needed to refine delivery mechanisms, minimize off-target risks, and address regulatory barriers. Progress in these areas could position siRNA multivalent vaccines as key components in global health strategies, especially for infectious disease and cancer management.
Keywords: Adverse immune reactions; Targeted therapy; combination therapy; delivery systems; lipid nanoparticles